Incorporation and optimization of RGO and GO in SSBR/NR composites expands their applicability. Issue 9 (November 2021) - Lin, Guangyi; Wang, Hong; Yu, Boquan; Liu, Shouyi; Liang, Zhenning; Liu, Fumin; Zeng, Runhang; Chen, Shaowei; Kuang, Tairong; Yu, Kaiben; Chi, Baihong
Natural rubber (NR) has poor mechanical properties, which limits its practical application. Filler blending is a simple method that improves the inherent properties of natural rubber and expand its applicability. Using the mechanical mixing process, the effects of graphene oxide (GO) and redox graphene (rGO) on the physical properties, electrical conductivity, thermal conductivity, and air permeability of styrene-butadiene rubber (SSBR)/NR composites were studied. The results show that rGO exhibits efficient filler properties in various aspects, for example, the optimal filling amount of rGO and GO was 1.5 phr. In addition, rGO filled SSBR/NR composites showed satisfactory filler dispersibility. Notably, the better dispersibility of rGO was because of fewer hydrophilic functional groups on the surface which were difficult to agglomerate. The increase of rGO and GO content increased the maximum torque (MH) and minimum torque (ML) of the composite material, and decreases tc90 and tc10. The Payne effect of GO/SSBR/NR composites is more obvious than that of rGO/SSBR/NR composites. In addition, we found that the content of rGO (GO) reached saturation at 2phr. Notably, rGO and GO improved the properties of rGO filled SSBR/NR composites such as the tensile strength of rGO/SSBR/NR composites to 23.9 MPa. This shows the potential application of SSBR/NR composites in wearable electronic devices.